Exploring the potential of online services in utilizing free software for educational activities - Vladyslav Ye. Velychko; Svitlana O. Omelchenko; Elena G. Fedorenko (Academy of Cognitive and Natural Sciences, 2023)
This article delves into the utilization of online services for studying and incorporating free software into educational settings. Free software embodies the principles of freedom and intellectual creativity, yet despite the existence of numerous software products within repositories, their integration into educational activities remains limited. Through questionnaires, analysis of open data, and reviewing existing research on the use of free software, this study identifies factors that facilitate or hinder its adoption in educational contexts. Drawing on the collected data, the article provides insights into the viability of incorporating free software into educational activities and showcases specific examples of its usage. Additionally, the study highlights the value of online resources in familiarizing educators and learners with free software, underscoring the central focus of this investigation. By shedding light on the potential benefits and challenges of leveraging free software in education and emphasizing the role of online services, this article contributes to the discourse surrounding the integration of free software in educational settings.